Perceived financial implication oftransforming conventional to shariah compliant businesses in Kelantan food industry / Emilsa Nazarih Badrol Risyam - Badrol Risyam, Emilsa Nazarih (2013)
By the year 2013, the Muslims population is going to be 37 percent of the global population. The halal food industry is essential to Muslims worldwide as it gives them a sense of security in shariah compliant basis. In particular, shariah principles affect the businesses in various fields, for instance, banking, fashion and apparel, cosmetics and body care as well as in pharmaceutical industries. Knowledge on halal food is so crucial to be studied as food industry becomes one of the main sources of income for local community in Kelantan. Aim of this research paper is to investigate perceived financial implication of transforming conventional to shariah compliant businesses in food industry. Business transformation initiative may deliver real benefits to the businesses by helping to improve efficiencies and better business position to thrive in the new economy of halal market. Theory of Reasoned Action (TRA) has been used to show the effect of behaviour intention on Kelantan food industry player in transforming their businesses to shariah compliant. Theory shows there are three factors affect the behaviour intention, they are, behavioural beliefs, outcome evaluation and motivation to comply. Cost consideration being considered as moderator to note if there is significant or insignificant relationship between each factor. To meet these objectives, a set of questionnaire was constructed to gather information on the issue. A total of 150 industry player from several niche areas in Kelantan were selected. This research finding is based on the Moderated Regression Analysis (MRA). The result shows that as cost consideration moderates the relationships, behavioural beliefs is a significant factor, while insignificant factor are outcome evaluation and motivation to comply. However, all factors have a positive relationship to behaviour intention of Kelantan food industry player in transforming conventional to shariah compliant businesses